Silencing Reading, Silencing the boys: Using action research to investigate silent reading programs and its effects on boys’ literacy skills - Rachel Velluto; Joanna Barbousas (Networks: An Online Journal for Teacher Research, 2013)
Despite the vast amount of literature regarding boys and their underperformance in the literacy realm, only some research indicates that boys’ low literacy levels may be attributed to unchallenged literacy classroom practices. Sustained Silent Reading (SSR) is a free voluntary reading program in which students are expected to read (usually books) for a period of time. Observing an SSR period during the teaching practicum as a pre-service teacher, the unstructured nature of the lesson disengaged many of the boys. In the lesson, the students are expected to select a book from the library and read in silence for the duration of forty minutes. How is one to know if our students are engaging in reading practices without some form of dialogue between their peers and the teacher that enables them to share their individual understanding? In the action research, the aim was to explore whether such a program is a vehicle for the production of critical literacy skills for male adolescents or if an accepted pedagogical practice, such as SSR is prohibiting our boys from attaining literacy in our schools. This paper refers to Kemmis (2009; 2006) to examine the guiding principles of action research.